2023
DOI: 10.1001/jamanetworkopen.2022.54303
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Early Autism Detection Models Based on Electronic Health Record Data Collected Before Age 1 Year

Abstract: ImportanceAutism detection early in childhood is critical to ensure that autistic children and their families have access to early behavioral support. Early correlates of autism documented in electronic health records (EHRs) during routine care could allow passive, predictive model-based monitoring to improve the accuracy of early detection.ObjectiveTo quantify the predictive value of early autism detection models based on EHR data collected before age 1 year.Design, Setting, and ParticipantsThis retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The initial cohort included all patients with an autism‐related ICD‐10‐CM diagnosis (F84.0, F84.5, F84.8, or F84.9) associated with encounters before 1st June 2021. Following a computable phenotype previously investigated at DUHS (Engelhard et al, 2023), our inclusion criteria were (a) diagnosis codes related to autism associated with ≥2 encounters; (b) ≥1 documented encounter of any type at least 2 years prior to the first autism code; and (c) an observed autism diagnosis code before age 18. Criterion (a) was designed to ensure patients received routine care within DUHS for a substantial period of time prior to autism diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial cohort included all patients with an autism‐related ICD‐10‐CM diagnosis (F84.0, F84.5, F84.8, or F84.9) associated with encounters before 1st June 2021. Following a computable phenotype previously investigated at DUHS (Engelhard et al, 2023), our inclusion criteria were (a) diagnosis codes related to autism associated with ≥2 encounters; (b) ≥1 documented encounter of any type at least 2 years prior to the first autism code; and (c) an observed autism diagnosis code before age 18. Criterion (a) was designed to ensure patients received routine care within DUHS for a substantial period of time prior to autism diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…How to cite this article: Gu, Z., Dawson, G., & Engelhard, M. (2023). Sex differences in the age of childhood autism diagnosis and the impact of co-occurring conditions.…”
Section: Funding Informationmentioning
confidence: 99%
“…In contrast to traditional screening tools that require expensive, time-consuming procedures, AI models can learn subtle patterns and precursors of disease, and then automatically identify at-risk patients using longitudinal information stored in EHRs [12,13]. For instance, models trained on routine EHR data have detected autism spectrum disorder in infants as early as 30 days after birth (nearly one year earlier than standard autism screening tools) [14], and they have detected latent diseases in adults such as peripheral artery disease [15]. They have also identified individuals at high risk of falling [16], and predicted the development of pressure ulcers within the first 24 hours of admission to an intensive care unit [17].…”
Section: Electronic Health Recordsmentioning
confidence: 99%
“…Previous work on autism prediction using electronic health records (EHRs) identified covariates that are associated with autism, such as low birth weight, small for gestational age, low Apgar scores, and other perinatal complications . More recently, Engelhard et al reported high predictive value of their EHR-based autism prediction model, applied before 1 year of age. Similarly, Onishchenko et al used medical claims data to estimate an autism comorbid risk score that aimed to improve the accuracy of M-CHAT.…”
Section: Introductionmentioning
confidence: 99%